2001
DOI: 10.1207/s15327914nc391_11
|View full text |Cite
|
Sign up to set email alerts
|

Food Frequency Questionnaire as a Screening Test

Abstract: We assessed the accuracy of a 141-item food frequency questionnaire as a screening test to detect high or low consumption of nutrients associated with cancer. Fifty-five men and 58 women participating in two population-based cohort studies in Miyagi, Japan, provided four three-day diet records over a one-year period and subsequently completed the questionnaire twice with a one-year interval. Pearson correlation coefficients between 17 nutrients measured by the diet records and the first questionnaire ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…20 Long-term sodium and potassium intakes A standardized method was used to calculate food consumption and related nutrients from data obtained in a Japanese version of the food-frequency questionnaire, which asked about the average frequency of consumption of each food during the previous year. 21 We previously confirmed that the foodfrequency questionnaire is reasonably reproducible and comparable with diet records, taking into account seasonal variations in food consumption. 21 A standard portion size of one serving was specified for each food, and respondents were asked if their usual portion was larger (41.5 times), the same or smaller (o0.5 times) than the standard.…”
Section: Physical and Biochemical Examinationssupporting
confidence: 65%
See 3 more Smart Citations
“…20 Long-term sodium and potassium intakes A standardized method was used to calculate food consumption and related nutrients from data obtained in a Japanese version of the food-frequency questionnaire, which asked about the average frequency of consumption of each food during the previous year. 21 We previously confirmed that the foodfrequency questionnaire is reasonably reproducible and comparable with diet records, taking into account seasonal variations in food consumption. 21 A standard portion size of one serving was specified for each food, and respondents were asked if their usual portion was larger (41.5 times), the same or smaller (o0.5 times) than the standard.…”
Section: Physical and Biochemical Examinationssupporting
confidence: 65%
“…21 We previously confirmed that the foodfrequency questionnaire is reasonably reproducible and comparable with diet records, taking into account seasonal variations in food consumption. 21 A standard portion size of one serving was specified for each food, and respondents were asked if their usual portion was larger (41.5 times), the same or smaller (o0.5 times) than the standard. We then estimated sodium and potassium intakes.…”
Section: Physical and Biochemical Examinationssupporting
confidence: 65%
See 2 more Smart Citations
“…The reproducibility and validity of this questionnaire were previously reported in detail. 29,30 The questionnaire asked about the average frequency of intake of each food during the previous year according to nine frequency categories ranging from no consumption to X7 times per day. A standard portion size of one serving was specified for each food, and respondents were asked whether their usual portion was larger (41.5 times), the same or smaller (o0.5) than the standard.…”
Section: Study Populationmentioning
confidence: 99%